The Similarity Renormalization Group - for three bosons in one-dimensional momentum space - Åkerlund, Oscar; Lindgren, Jonathan; Lerner, Pablo; Linscott, Ross; Grevholm, Björn; Bergsten, Johan (My University, 2011)
The Similarity Renormalization Group (SRG) has been studied in a one-dimensional system. It has been implemented for two- and three-body systems in continuous momentum space using Jacobi coordinates. Various potentials have been used, describing different physical attributes such as hard-core repulsion and long-range attraction. The unitarity of the transformation has been verified by examining the conservation of observables, for example of the binding energy. The importance of the induced three-body force has been addressed. We show that the decoupling of high and low energies occurs and that because of this computational requirements are lowered.
Keywords: Grundläggande vetenskaper; Fysik; Lågenergifysik; Beräkningsfysik; Basic Sciences; Physical Sciences; Low energy physics; Computational physics